PERSONAL EMPOWERMENT AS DETERMINANTS OF ORGANISATIONAL OPPORTUNITY - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Abdullah, Muhammad Faris (PLANNING MALAYSIA, 2019)
Architects can influence workplace behaviours and manoeuvre workers’ emotions through aligning design strategies with human moods. Design sustains organisational well-being through strengthening space occupants’ empowerment, leading to better work performances. Issue: Existing research has limited empirical evidence on the impact of personal empowerment (PE) on organisational opportunity (OO). Purpose: This paper aims to verify the statistical predictability of OO based on PE. Approach: Multiple Correlation and Multiple Linear Regression were carried out to assess linear associations and parameters of linear equations to predict OO components based on PE items. Findings: OO components were predictable by the majority of the PE items and ‘monitoring behaviours to suit with situation’ was the strongest predictor of OO.